FIKIH LINGKUNGAN DALAM PETA PEMBANGUNAN NASIONAL - Yaqub, Andi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Conservation of the environment is a form or mode of management and protection of all things related to human life wisely and sustainably. Understanding of the environment is closely related to the realization of the ideals of the nation and the country. Therefore, the projection of understanding is arranged in the national development map. One of the ideal perspective is the deep understanding of the environment and the philosophy of the nation of Islamic jurisprudence/islamic law. Beginning the concept of environmental conservation focuses on the love of nature as a manifestation of servantship to Allah swt. The teleological review positioned the approach of environmental jurisprudence as the ideal framework for environmental conservation. The substance of jurisprudence / Islamic law emphasizes the paradigm of goodness that delivers individual consciousness and social consciousness. Environmental jurisprudence can be contained in the law substance, in the Law as well as government regulations, whether located at the center, and at the region. The implementation phase also positions the strengthening of Islamic law as an ethical approach and also as a social control. The rules on environmental conservation in Indonesia are categorized under environmental law, environmental science and environmental politics.